Foreign assistance in a climate-constrained world - Channing Arndt; Christian Friis Bach (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The emergence of climate finance has the potential to catalyze positive changes in the institutional architecture and distribution mechanisms for financial flows to lower income countries. The nature of the challenge of development in the context of climate change argues for recipient country leadership in the implementation of co-ordinated development, adaptation, and mitigation strategies based on predictable and long-term financial flows. Transparent and effective information systems in recipient countries should be a key prerequisite to the initiation and continuation of these flows. While some positive steps have been taken, there remains a very long way to go addressing the interlinked development, adaptation, and mitigation challenges of the twenty-first century.
Keywords: O10; O19; Q56; 330; climate change; development assistance; mitigation; adaptation; Klimaveränderung; Finanzierung; Entwicklungshilfe